Respuesta :

We start by writing the ratio [tex]x:y[/tex] and [tex]a:b[/tex] as fraction

[tex] \frac{x}{x+y}: \frac{y}{x+y} = \frac{a}{a+b}: \frac{b}{a+b} [/tex]

This shows two pairs of equivalent fractions

[tex] \frac{x}{x+y}= \frac{a}{a+b} [/tex] and [tex] \frac{y}{x+y}= \frac{b}{a+b} [/tex]

We will use the first pair of fraction
[tex] \frac{x}{x+y}= \frac{a}{a+b} [/tex] ⇒ cross multiply gives
[tex]x(a+b)=a(x+y)[/tex] ⇒ then rearrange
[tex] \frac{a+b}{x+y} = \frac{a}{x} [/tex] ⇒ which we can also write in form of ratio
[tex](a+b):(x+y)=a:x[/tex]

Hence it is proved that [tex]a:x=(a+b):(x+y)[/tex] as required
ACCESS MORE